2017
DOI: 10.1108/ijchm-06-2015-0293
|View full text |Cite
|
Sign up to set email alerts
|

Examine destination loyalty of first-time and repeat visitors at all-inclusive resorts

Abstract: Purpose The purpose of this study is to examine the factors that are likely to influence the loyalty behavior of first-time and repeat visitors to all-inclusive resorts. Design/methodology/approach Data were collected from first-time and repeat Russian tourists to Antalya, Turkey, utilizing a self-administered survey questionnaire. A total of 339 usable responses were obtained. A structural equation modeling approach was used to test the proposed model on the first-time and repeat visitors’ samples. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 76 publications
(100 reference statements)
5
47
1
Order By: Relevance
“…Service quality and customer satisfaction has a direct impact on retention and loyalty to a specific tourist product or destination (Hemsley-Brown and Alnawas, 2016; Kandampully, Zhang, and Bilgihan, 2015;Rahimi, 2017;Rahimi and Gunlu, 2016;Rauch et. al., 2015;Yolal, Chi and Pesämaa, 2017). Previous studies found different key factors for travellers' satisfaction with allinclusive packages (Lo and Lam, 2004;Ozdemir et al, 2012;Yolal et al, 2017).…”
Section: Satisfaction Level Of Travellers With All-inclusive Travel Pmentioning
confidence: 97%
“…Service quality and customer satisfaction has a direct impact on retention and loyalty to a specific tourist product or destination (Hemsley-Brown and Alnawas, 2016; Kandampully, Zhang, and Bilgihan, 2015;Rahimi, 2017;Rahimi and Gunlu, 2016;Rauch et. al., 2015;Yolal, Chi and Pesämaa, 2017). Previous studies found different key factors for travellers' satisfaction with allinclusive packages (Lo and Lam, 2004;Ozdemir et al, 2012;Yolal et al, 2017).…”
Section: Satisfaction Level Of Travellers With All-inclusive Travel Pmentioning
confidence: 97%
“…Yolal et al [38] Urban tourism SEM This study shows that differences exist between the two groups of visitors-first time visitors value cognitive attributes more and rely more on cognitive evaluation.…”
Section: Verma Rajendran [37] Cultural Heritage Site Semmentioning
confidence: 99%
“…Those positive perceptions and attitudes have critical importance for enterprises aiming at gaining competitive advantage (Kandampully, Zhang, & Jaakkola, 2018;Kumar & Pansari, 2016;Soudagar, Iyer, & Hildebrand, 2012). Individuals with positive organizational perceptions and attitudes are very likely to become loyal consumers (Lee & Kim, 2018;Rajaguru & Hassanli, 2018;Xie & Chen, 2014;Yolal, Chi, & Pesämaa, 2017). Advantages of loyalty will bring remarkable easiness to the enterprise in terms of gaining competitive advantage.…”
Section: Solutions and Recommendationsmentioning
confidence: 99%